The Influence of Teacher Benefits on Instructional Enthusiasm and Professional Engagement - Nankhuni, Felix Tithokoze; Odoyo, Collins Otieno (Journal of Educational Research and Policies, 2026)
This study investigated the influence of fringe, remuneration, and salary increase on the motivation, job satisfaction, and enthusiasm of teachers. Drawing on survey data, it examined key factors such as the perception of fair pay, performance-based incentives, opportunities for additional income, and the provision of benefits. The findings indicated that teachers generally perceived remuneration and benefits as significant contributors to their motivation and engagement at work. Similarly, salary increases were seen as instrumental in improving financial stability, enhancing motivation, and boosting morale. The results suggested a strong positive relationship between the provision of benefits and the level of teacher enthusiasm. Among the compensation elements examined, salary increases emerged as the most influential factor affecting motivation, while remuneration alone did not exhibit a notable impact. These insights pointed to the crucial role of structured and equitable compensation practices in supporting teacher well-being and commitment. The study highlighted the need for educational institutions to implement transparent reward systems, enhance benefit packages, and offer regular and fair salary adjustments to foster a motivated and satisfied teaching workforce. Such measures were deemed essential not only for improving teacher retention but also for enhancing overall school performance. Future research was encouraged to explore how long-term compensation strategies might influence both teacher effectiveness and student learning outcomes over time.